Combined sputum hypermethylation and eNose analysis for lung cancer diagnosis. Issue 8 (10th June 2014) - Hubers, A Jasmijn; Brinkman, Paul; Boksem, Remco J; Rhodius, Robert J; Witte, Birgit I; Zwinderman, Aeilko H; Heideman, Daniëlle A M; Duin, Sylvia; Koning, Remco; Steenbergen, Renske D M; Snijders, Peter J F; Smit, Egbert F; et al.
Abstract : Aims: The aim of this study is to explore DNA hypermethylation analysis in sputum and exhaled breath analysis for their complementary, non-invasive diagnostic capacity in lung cancer. Methods: Sputum samples and exhaled breath were prospectively collected from 20 lung cancer patients and 31 COPD controls (Set 1). An additional 18 lung cancer patients and 8 controls only collected exhaled breath as validation set (Set 2). DNA hypermethylation of biomarkers RASSF1A, cytoglobin, APC, FAM19A4, PHACTR3, 3OST2 and PRDM14 was considered, and breathprints from exhaled breath samples were created using an electronic nose (eNose). Results: Both DNA hypermethylation markers in sputum and eNose were independently able to distinguish lung cancer patients from controls. The combination of RASSF1A and 3OST2 hypermethylation had a sensitivity of 85% with a specificity of 74%. eNose had a sensitivity of 80% with a specificity of 48%. Sensitivity for lung cancer diagnosis increased to 100%, when RASSF1A hypermethylation was combined with eNose, with specificity of 42%. Both methods showed to be complementary to each other (p≤0.011). eNose results were reproducible in Set 2. Conclusions: When used in concert, RASSF1A hypermethylation in sputum and exhaled breath analysis are complementary for lung cancer diagnosis, with 100% sensitivity in this series. This finding should be further validated.